(untitled) (Al-Academy, 2025)
This research aims to investigate and analyze the aesthetic characteristics of the formations of the "Ain Heet" water cave as a source of visual and artistic inspiration. It explores the potential of employing these cave formations in the creation of contemporary ceramic artworks, addressing both form and content. Furthermore, the study seeks to develop artistic designs derived from the unique structures of the "Ain Heet" water cave, thereby contributing to the enhancement of tourism in the Kingdom of Saudi Arabia. The paper examines the aesthetic and geological features of Saudi caves and their role in shaping a distinctive artistic identity that reflects the natural and cultural diversity of the region. Methodologically, the study adopts a descriptive-analytical approach to the theoretical framework in conjunction with an experimental methodology for the practical component. The findings underscore the potential of deriving innovative artistic visions from Saudi nature, which serve both to preserve national identity and to strengthen the tourism sector through contemporary ceramic practices. Moreover, the study broadens the scope for producing ceramic artworks inspired by Saudi caves, suitable for display in exhibitions, museums, and touristic sites. The research concludes with key recommendations: enhancing local artists’ awareness of natural heritage as a vital source of artistic inspiration, encouraging the integration of natural environmental elements from Saudi Arabia into ceramic art, and promoting their utilization in research and artistic practices across ceramics and related disciplines.